MENDETEKSI FAKTOR PENENTU STRUKTUR MODAL PADA SUB SEKTOR PERDAGANGAN BESAR (WHOLESALER) DAN RETAILER DI INDONESIA YANG GO PUBLIK - Suharna, Jaka; Bertuah, Eka (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
This research aims to detect the determining factor of capital structure in Wholesaler and Retailer subsector in Indonesia. There are 44 companies used as the research sample; they are the wholesaler and retailer companies as listed in BEI (Indonesia Stock Exchange) during 2013-2017. The data analysis used logistic regression and ANOVA test. The result shows that the sales growth and profitability could be the determining factor in company capital structure. The sales growth has negative effect toward the capital structure. This implies that the higher sales growth, the lesser the debt usage. Besides, profitability has negative effect toward the capital structure. This indicates that the companies with profitability increased would reduce the debt usage as the profit would be used as funding to keep the innovation going in the company. The research result also shows that there are no differences in firm’s values between the high-debt-funding companies and the low-debt-funding companies. This supports the Modigliani-Miller theory which stated that the capital structure doesn’t affect the firm’s values. Keywords: capital structure, sales growth, profitability